Basic sciences curriculum in medical education - RITA REZAEE; VAHID KESHTKAR (Journal of Advances in Medical Education and Professionalism, 2013)
Introduction: Traditional methods are generally used for teaching basic science courses at Shiraz Medical School. Such courses are taught during the first and second years of a seven-year medical program. The goal of this study was to analyze teachers and students’ perceptions of basic science teaching in medical education. Methods: A descriptive cross-sectional study was conducted at the college of medicine of Shiraz University of Medical Sciences. Results: Regarding the students’ viewpoints, 71.4% reported that curriculum content in basic sciences was enough and had good relevance. 59.2% of students believed the objectives of basic sciences curriculum were clear. Conclusion: The burden of teaching basic sciences ranges from sustaining interest to clinical relevance. It is expected that medical schools will continuously monitor what works and what does not work with their curricula and make the necessary adaptations as required.